The Influence of Opportunities to Learn and Efficacy Belief Factor towards Mathematical Knowledge for Teaching - Lumbantoruan, Jitu Halomoan (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
This study investigates the effect of learning opportunities and beliefs on the efficacy of teaching mathematics on knowledge of mathematics for teaching. Using a structured questionnaire along with paper and pencil tests adapted from the literature review, data were collected from 187 prospective primary school teachers at the Indonesian Teacher Education Institute. Data were analyzed using Smart PLS 3.0. The results of the structural equation model show that both opportunities to learn-Practicum (β = 0.395, p < 0.001) and opportunities to learn -Program (β = 0.324, p < 0.001) are positively related to mathematics. The second regression analysis is to examine the influence of teaching efficacy beliefs on mathematics. The results showed that beliefs about expectations of learning outcomes in mathematics (β = 0.322, p < 0.001) were positively related to mathematics, while personal mathematics teaching efficacy beliefs (β = 0.017, p > 0.1) were not related to mathematics. Overall, the confidence factor and opportunities to learn explain the total 54% variance in mathematics. The implications of these findings for the successful implementation of teacher education programs in Indonesia are further elaborated.